The effects of design parameters on mechanical failure of Ti-6Al-4V implants using finite element analysis. (March 2020) - Bayata, Fatma; Yildiz, Cengiz
Highlights: The implant models with long-term service life and high fracture resistance were developed. The design parameters were optimized in order to prevent the failure of implants under cyclic biting loads. The implant model displaying the best biomechanical behavior under all biting conditions was determined. The result of this study can be utilized in the production of customizable implants having high fracture strength. Abstract: The failure of dental implant is frequently occurred as the result of mechanical complications under daily biting forces. The long-term stability and the success of a dental implant are highly depended upon developing an implant system having high fracture resistance under cyclic biting forces. The design of implant has a crucial role in improving the fracture resistance of implant by decreasing stress concentration around the implant system. In the present study, three-dimensional (3D) models of the internally connected Ti-6Al-4V implant systems were developed in different dimensions and the failure analysis of these implants was performed under real biting forces according to ISO 14801 using Finite Element Analysis (FEA). In these models, the design parameters (implant diameter, abutment diameter, taper angle of abutment, implant wall thickness, etc.) were optimized in order to prevent the failure of implants in long-term use. The implant model exhibiting the best biomechanical behavior was determined and the stress value was decreased to 170.34 MPa (von-Mises stress) in this implant under cyclic biting loads. Besides the high fracture resistance of this model, longer service life was predicted and relatively smoother stress transmission was achieved from the implant to the bone tissues under biting forces. The implant stability was also increased by optimizing implant tightening torques. Additionally, the mechanical behavior of this implant model was investigated under different biting conditions.